The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/wcms.1478
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐learning scoring functions for structure‐based virtual screening

Abstract: Molecular docking predicts whether and how small molecules bind to a macromolecular target using a suitable 3D structure. Scoring functions for structure-based virtual screening primarily aim at discovering which molecules bind to the considered target when these form part of a library with a much higher proportion of non-binders. Classical scoring functions are essentially models building a linear mapping between the features describing a proteinligand complex and its binding label. Machine learning, a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 134 publications
0
108
0
1
Order By: Relevance
“…For instance, a retrospective analysis based on random decoys found that a ML-based SF (MIEC-SVM) was much more predictive than a classical SF (Autodock4.2) on the ALK target, which was exactly what was later observed prospectively [8]. This is not the only ML-based SF reporting excellent prospective SBVS results without any use of PM decoys [14,34]. It is important to note too that PM decoys are not required either to train or test QSAR models [35], despite predicting exactly the same in vitro potency/affinity endpoints as SFs (e.g.…”
Section: Selecting a Scoring Function Based On Your Own Evaluationmentioning
confidence: 67%
See 3 more Smart Citations
“…For instance, a retrospective analysis based on random decoys found that a ML-based SF (MIEC-SVM) was much more predictive than a classical SF (Autodock4.2) on the ALK target, which was exactly what was later observed prospectively [8]. This is not the only ML-based SF reporting excellent prospective SBVS results without any use of PM decoys [14,34]. It is important to note too that PM decoys are not required either to train or test QSAR models [35], despite predicting exactly the same in vitro potency/affinity endpoints as SFs (e.g.…”
Section: Selecting a Scoring Function Based On Your Own Evaluationmentioning
confidence: 67%
“…Intelligence (AI), have demonstrated remarkable accuracy on various drug design applications [9][10][11][12][13][14]. In particular, when re-scoring crystal structures with ligand-bound proteins, or even their redocked poses, SFs are now able to predict the affinities of these binding molecules with high accuracy on many targets (we just wrote a review [13] focusing on this problem and discussing many examples from the literature).…”
Section: Sfs Built With Machine Learning (Ml) Arguably the Most Devementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a retrospective analysis based on random decoys found that a ML-based SF (MIEC-SVM) was much more predictive than a classical SF (Autodock4.2) on the ALK target, which was exactly what was later observed prospectively [8]. This is not the only ML-based SF reporting excellent prospective SBVS results without any use of PM decoys [14,34]. It is important to note too that PM decoys are not required either to train or test QSAR models [35], despite predicting exactly the same in vitro potency/affinity endpoints as SFs (e.g.…”
Section: Selecting a Scoring Function Based On Your Own Evaluationmentioning
confidence: 67%